Representasi Maskulinitas Pria dan Komodifikasi Simbol Agama dalam Iklan Gamis Zafeer Indonesia - Asvi Raihan; Raudha Yulindra Anggun Pratiwi; Alya Raihani Maulana; Fajar Junaedi (Universitas Muhammadiyah Klaten, 2025)
In providing information to consumers, advertisements usually use a symbol that triggers various perceptions among the audience. As in this research, which aims to provide an overview of the commodification of religion and the representation of masculinity occurring in the Gamis Zafeer Indonesia advertisement, so that business actors in creating advertising concepts are more careful with public perceptions in the future and respect religion. This research method uses qualitative descriptive analysis with Roland Barthes' semiotic analysis, aiming to explain the denotative, connotative, and mythic meanings generated in the Zafeer Indonesia gamis advertisement, as well as the representation of masculinity formed within the advertisement. The results of this discussion indicate that the advertisers aim to provide information and encourage consumers to use the gamis product. By using religious symbols and creating representations of masculinity to attract public sympathy.